The Determinants of Access to External Financing for Growth Companies: The Singular Case of Cameroon (Global Journal of Management and Business Research, 2020)
The purpose of this study is to identify the factors that determine the external financing of growing small companies in Cameroon. From the econometric analyzes using the logistic regression method on data collected by questionnaire on a sample of 105 growing companies all located in the Cameroonian context, these analyzes show that the entrepreneur's belonging to a relational network, the acquisition of new technologies and the results of the R & D process promote access to external financing for innovative small companies.
Keywords: external financing; growing companies; innovation; stages theory of company2019; s development; access to finance